2017
DOI: 10.1080/10245332.2016.1277006
|View full text |Cite
|
Sign up to set email alerts
|

Occupational, dietary, and other risk factors for myelodysplastic syndromes in Western Greece

Abstract: Purpose: We have observed an increasing incidence of myelodysplastic syndromes (MDS) in the geographic area of Western Greece during the past two decades. The objective of this study was to investigate potential risk factors for the manifestation of MDS in this area of Greece. Methods:A hospital-based case-control study was conducted in the public hospitals of the region. Participants were interviewed based on a questionnaire regarding demographics, occupational exposures, smoking, alcohol consumption, dietary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 40 publications
0
15
0
1
Order By: Relevance
“…The exposure to synthetic phytoiatric prod-ucts such as insecticides, herbicides, fungicides, and fertilizers is the reasons for the main difference between the two scenarios. Indeed, the COG scenario exposes workers, with a strong association, to the risks of colorectal carcinoma (1.176 hours), asthma (588 hours), myelodysplastic syndromes (588 hours), REM sleep behaviour disorder (300 hours), muscle weakness (212 hours), numbness (212 hours) and cutaneous melanoma (89 hours) (Salameh et al, 2006;Lo et al, 2010;Postuma et al, 2012;Fortes et al, 2016;Avgerinou et al, 2017;Hongsibsong et al, 2017). In addition, with a moderate association, the COG scenario exposes workers to the risks of amyotrophic lateral sclerosis (588 hours), renal cell carcinoma (89 hours) and non-Hodgkin lymphoma (89 hours) (Hu et al, 2002;Fritschi et al, 2005;Hohenadel et al, 2011;Kang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…The exposure to synthetic phytoiatric prod-ucts such as insecticides, herbicides, fungicides, and fertilizers is the reasons for the main difference between the two scenarios. Indeed, the COG scenario exposes workers, with a strong association, to the risks of colorectal carcinoma (1.176 hours), asthma (588 hours), myelodysplastic syndromes (588 hours), REM sleep behaviour disorder (300 hours), muscle weakness (212 hours), numbness (212 hours) and cutaneous melanoma (89 hours) (Salameh et al, 2006;Lo et al, 2010;Postuma et al, 2012;Fortes et al, 2016;Avgerinou et al, 2017;Hongsibsong et al, 2017). In addition, with a moderate association, the COG scenario exposes workers to the risks of amyotrophic lateral sclerosis (588 hours), renal cell carcinoma (89 hours) and non-Hodgkin lymphoma (89 hours) (Hu et al, 2002;Fritschi et al, 2005;Hohenadel et al, 2011;Kang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…reported a significant positive association between coffee consumption and the risk of MDS in a case‐control study of 80 MDS cases and 160 controls in Serbia Montenegro, with an odds ratio (OR) of 4.8 (95% CI, 2.2–10.8) for coffee drinkers relative to non‐drinkers . Another case‐control study in western Greece of 126 MDS cases and 102 controls did not observe a significant association . However, these results might have been affected by potential confounders, including smoking, for which they were not adjusted.…”
Section: Discussionmentioning
confidence: 95%
“…21 Another case-control study in western Greece of 126 MDS cases and 102 controls did not observe a significant association. 22 However, these results might have been affected by potential confounders, including smoking, for which they were not adjusted. With regard to green tea, only one case-control study in China (208 cases and 208 controls) has evaluated the effect, and this reported a significant dose-dependent protective effect of tea consumption (mainly green tea) with the risk of MDS after adjustment for potential confounders (nondrinkers: reference, 1 cup/day: HR 5 0.25, 0.11-0.61; 2 cup/day: HR 5 0.44, 0.22-0.89, p for trend 5 0.02).…”
Section: Significant Association Between Coffee Consumption and The Rmentioning
confidence: 95%
“…Tumor is a group of cells/tissues that has lost its control on the normal growth at the gene level due to the activation of various oncogenes or inactivation of tumor suppressors (Noda et al, 1999;Zhang et al, 2013). According to the size and growth characteristics, tumor tissue can be divided into malignant (cancerous) and benign (non-cancerous) (Avgerinou et al, 2017). Malignant tumor grows rapidly and often infiltrate to the surrounding tissues without envelops on the surface.…”
Section: Introductionmentioning
confidence: 99%